Agriculture оf Artsakh: Historical Overview - Minasyan, Manush Marlest; Kocharyan, Tsovinar Vruyr (ՀՀ ԳԱԱ ՏԻ)
During the period of independence, agriculture was always the focus of the Artsakh government, and the budgetary injections in the sector were quite large, nevertheless, in recent years, the sector provided a small part of the GDP. The relevance of the article is determined by the analysis of the development process of the sector with strategic importance for the Artsakh economy. The geopolitical tensions, and the closed borders, when the only opportunity to connect the world was the Republic of Armenia and it was very difficult and expensive for the farmers to export their products or import production means negatively affected the agriculture of Artsakh. The purpose of the article is to present the history of the development, recorded indicators, and main achievements of one of the important sectors of the economy of the Republic of Artsakh– agriculture. The purpose of the article is to present the history of the development of agriculture in the Republic of Artsakh. Անկախության շրջանում գյուղատնտեսությունը Արցախի Հանրապետության կառավարության ուշադրության կիզակետում է միշտ եղել, բավական մեծ էին բյուջետային ներարկումներն ոլորտում, սակայն, վերջին տարիներին ճյուղն ապահովում էր ՀՆԱ-ի չնչին մասը: Հոդվածի արդիականությունը պայմանավորված է Արցախի տնտեսության համար ռազմավարական նշանակություն ունեցող ճյուղի զարգացման ընթացքի վերլուծությամբ: Արցախի գյուղատնտեսության վրա բացասաբար են անդրադարձել երկրի չճանաչվածությունը, աշխարհաքաղաքական լարվածությունը, փակ սահմանները, երբ աշխարհին կապող միակ հնարավորությունը Հայաստանի Հանրապետությունն էր և գյուղացու համար շատ դժվար ու թանկ էր իր արտադրանքն արտահանելը կամ արտադրության միջոցներ ներմուծելը: Հոդվածի նպատակն է ներկայացնել Արցախի Հանրապետության տնտեսության կարևոր ճյուղերից մեկի՝ գյուղատնտեսության, զարգացման պատմութ-յունը, արձանագրած ցուցանիշները, հիմնական ձեռքբերումները: В период независимости сельское хозяйство всегда находилось в центре внимания правительства Республики Арцах, бюджетные вливания в отрасль были достаточно большими, однако в последние годы отрасль обеспечивала незначительную часть ВВП. Актуальность статьи обусловлена анализом процесса развития отрасли, имеющей стратегическое значение для экономики Арцаха. Непризнанность страны, геополитическая напряженность, закрытые границы, когда Республика Армения была единственным способом соединения мира, а фермеру было очень сложно и дорого экспортировать свою продукцию или импортировать средства производства, оказали негативное влияние на сельское хозяйство Арцаха. Цель статьи–представить историю развития одной из важных отраслей экономики Республики Арцах–сельского хозяйства, зафиксированные показатели, основные достижения.
Keywords: Agricultural Economics; Artsakh